APLIKASI PELAPISAN DENGAN EMULSI ASAM OLEAT, ASAM STEARAT, DAN ASAM PALMITAT DALAM PENGAWETAN BUAH SALAK BALI SEGAR - Wisnu Matra Atmaja, Ida Bagus; Wayan Gunam, Ida Bagus; Wrasiati, Ni Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2015)
This study aims to determine the effect of the emulsion coating with oleic acid, stearic acid and palmitic acid in bali fresh fruits characteristics and determine the proper emulsion formulation to obtain fresh bali best fruit characteristics. Experimental design used in this research is completely randomized design ( CRD ) is simple. The treatment is performed as follows; A0: Salacca untreated ( control ). A1: Salacca treatment given oleic acid ( 1 % ), distilled water ( 98 % ), tween 80 ( 0.5 % ), NaHCO3 ( 0.5 % ). A2: Salacca treatment given stearic acid ( 1 % ), distilled water ( 98 % ), tween 80 ( 0.5 % ), NaHCO3 ( 0.5 % ). A3: Salacca treatment given palmitic acid ( 1 % ), distilled water ( 98 % ), tween 80 ( 0.5 % ), NaHCO3 ( 0.5 % ). A4: Salacca treatment given oleic acid ( 1 % ), stearic acid ( 1 % ), palmitic acid ( 1 % ), distilled water ( 96 % ), tween 80 ( 0.5 % ), NaHCO3 ( 0.5 % ), The experiment was repeated three ( 3 ) times. Observations durability shelf life is done every 3 days until the fifteenth day. The results showed that the emulsion layer with oleic acid, stearic acid and palmitic acid can significantly extend the shelf life of fruits bali. By protecting the surface of the rind of the fruit so as to prevent contamination with bacteria or microbes destroyer .   Keyword : coating, oleic acid, stearic, palmitic, fres h Salak fruits
Keywords: 78